Lyme Disease - Phillip E. Kaufman; Philip G. Koehler; Jerry F. Butler (EDIS)
Revised! ENY-209, a 3-page illustrated fact sheet by P.E. Kaufman, P.G. Koehler, and J.F. Butler, describes the symptoms, treatment, prevention and control of this disease whose primary vector is the black-legged deer tick. This version expands and updates the previous version to include current statistics and recommendations, and adds illustrations, online resources and a reference list. Part of the Master Gardener Handbook. Published by the UF Department of Entomology and Nematology, August 2006.